2023
DOI: 10.3389/fenvs.2022.1091859
|View full text |Cite
|
Sign up to set email alerts
|

How to drive corporate responsible innovation? A dual perspective from internal and external drivers of environmental protection enterprises

Abstract: Responsible innovation has been widely concerned by the public sector and actively explored by scholars for its great role in supporting eco-innovation and sustainable development. However, as the main body of innovation, enterprises have not been fully recognized. Moreover, the research on the driving factors of responsible innovation is mostly the direct influence of a single factor, lacking the overall consideration of the internal and external environment. To bridge this research gap, this study, by deeply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…To balance the interests of all parties, companies increasingly focus on responsible leadership. Environmental responsible leadership (Chianghui, 2023;Yi et al, 2023) builds a communication platform that includes many stakeholders, allowing employees to better understand the needs of each party rather than acting blindly based on their own experiences and assumptions, and facilitating employees' clarity about the company's position and direction of pro-environmental behavior. (Voegtlin et al, 2020) clarified that responsible leaders have three roles: citizen, expert, and facilitator.…”
Section: Theoretical Basis and Research Hypothesis 21 Environmental R...mentioning
confidence: 99%
“…To balance the interests of all parties, companies increasingly focus on responsible leadership. Environmental responsible leadership (Chianghui, 2023;Yi et al, 2023) builds a communication platform that includes many stakeholders, allowing employees to better understand the needs of each party rather than acting blindly based on their own experiences and assumptions, and facilitating employees' clarity about the company's position and direction of pro-environmental behavior. (Voegtlin et al, 2020) clarified that responsible leaders have three roles: citizen, expert, and facilitator.…”
Section: Theoretical Basis and Research Hypothesis 21 Environmental R...mentioning
confidence: 99%
“…It is noteworthy that commercialisation is a pivotal phase in innovation, and most innovations are founded and produced by the private sector [23,45]. With growing interest in the theme of 'being responsible' in technospheres, some influential technology companies have embraced the RIT concept to respond to societal needs and challenges by creating responsible products and services [24,28,46]. These companies have established various principles based on their own perspectives, missions, or specific business backgrounds to help guide their product and services to respond to the concept of RIT, e.g., Microsoft's Responsible AI, Amazon's Responsible Use of Machine Learning, Samsung's Responsible Production and Sales, and Atlassian's Responsible Technology.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…RIT in a business context refers to the emerging concept where businesses actively consider the broader societal, ethical, and environmental implications of their innovations and technological deployments [10,23,47]. Li et al [24] and Jarmai [48] posited that the impetus for corporates to adopt a responsible approach in their innovation process primarily stems from both internal factors, such as company vision and the pursuits of key individuals, and external factors, including market demand, policy pressure, and the expectations of civil society. Some studies indicated that incorporating the RIT concept into business strategies contributes to leading long-term benefits, including enhanced brand reputation, increased trust among consumers and stakeholders, and a more sustainable and resilient business model [27,[49][50][51].…”
Section: Literature Backgroundmentioning
confidence: 99%
See 2 more Smart Citations